Report on: "The 1st Workshop on National Immunization Programs and Vaccine Coverage in ASEAN Countries, April 30, 2015, Pattaya, Thailand" - Weerawan Hattasingh (2018)
© 2016. The 1st Workshop on National Immunization Programs and Vaccine Coverage in Association of Southeast Asian Nations (ASEAN) Countries Group (WNIPVC-ASEAN) held a meeting on April 30, 2015, Pattaya, Thailand under the auspices of the Pediatric Infectious Diseases Society and the World Health Organization (WHO). Reports on the current status and initiatives of the national immunization program (NIP) in each ASEAN countries that attended were presented. These reports along with survey data collected from ministries of health in ASEAN countries NIPs demonstrate that good progress has been made toward the goal of the Global Vaccine Action Plan (GVAP). However, some ASEAN countries have fragile health care systems that still have insufficient vaccine coverage of some basic EPI antigens. Most ASEAN countries still do not have national coverage of some new and underused vaccines, and raising funds for the expansion of NIPs is challenging. Also, there is insufficient research into disease burden of vaccine preventable diseases and surveillance. Health care workers must advocate NIPs to government policy makers and other stakeholders as well as improve research and surveillance to achieve the goals of the GVAP.